Analysis of the associated factors for severe weight loss after minimally invasive McKeown esophagectomy. Issue 2 (21st December 2018) - Wang, Peiyu; Li, Yin; Sun, Haibo; Zhang, Ruixiang; Liu, Xianben; Liu, Shilei; Wang, Zongfei; Zheng, Yan; Yu, Yongkui; Chen, Xiankai; Li, Haomiao; Zhang, Jun; et al.
Abstract : Background: This study investigated the risk factors for severe weight loss (SWL) within one year after minimally invasive McKeown esophagectomy. Methods: Esophageal cancer patients who underwent McKeown esophagectomy between January and July 2017 were prospectively enrolled. Preoperative body weight (PBW) was chosen as the initial body weight. Results: Forty‐four patients were enrolled and successfully followed up for one year. Median weight loss was 7.4% (quartile: 5.3–8.1%) and 12.6% (quartile: 8.8–17.7%) four weeks and one year after surgery, respectively. Accelerated weight loss occurred during the first two weeks after discharge, with median weight loss of 5.6% (quartile: 4.2–7.1%). Multivariable analysis showed that age ≥ 70 years (odds ratio [OR] 7.65; P = 0.030), preoperative sarcopenia (OR 7.18; P = 0.030), the first surgery in the daily schedule (OR 6.87; P = 0.032) and vocal cord paralysis (OR 12.30; P = 0.046) were independent risk factors for short‐term (4 weeks) SWL (> 7.5% PBW), while an American Society of Anesthesiologists score of 3–4 (OR 6.58; P = 0.047), a high fat‐free mass (OR 21.91; P = 0.003), and vocal cord paralysis (OR 25.83; P = 0.017) were independent risk factors for long‐term (1 year) SWL (> 13.0% PBW) after esophagectomy. Postoperative symptoms of insomnia, appetite loss, dysphagia, eating difficulties, and taste issues were also related to SWL. Conclusions: In esophageal cancer patients who have undergone esophagectomy, the first two weeks after hospital discharge is a key period for nutrition intervention. Patients with associated factors for SWL require postoperative nutrition support.